KAJIAN INFRASTRUKTUR DAN SEMPADAN SUNGAI PADA WILAYAH RAWAN BANJIR LAHAR DI SUNGAI PROGO HILIR - Jazaul Ikhsan; Krisna Bagus Anjasmara (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2020)
Progo River is one of the rivers that originated in Merapi Mountain. It is one of the active volcanoes, and if it erupted, so it resulted in an abundant material or sediment. The material from its eruption transported by water discharge will become a debris flow, that it gave damage and losses on infrastructure and inhabitants living around riparian areas. Based on the background, therefore, it is essential to do a research-related infrastructure and population in a riparian zone. The research objective is to study the accordance of the condition of the riparian zone of downstream Progo River based on the established rules. The method used was a field survey assissted by the application of Survey123 for ArcGIS. The data processing used ArcGIS software. The research result shows that some locations are not by the established rules on riparian areas. One of the most significant places having the highest settlement percentage included in riparian areas is Jatisarono Village Nanggulan Subdistrict, with the area of settlement of 0.1224 km square and 44.07% for the riparian zone with 50 m width and 0.1766 km square while 21.16% for the riparian zone with 100 m width. Jatisarono village also becomes the village with the highest approximate population number within the riparian zones with 135 people in the riparian zone with 50 m width and 195 people the riparian zone with 100 m width. From the field survey result, it finds that 13 rivers infrastructures along the downstream Progo River consisting of 10 bridges, two dams, and one groundsill (sample) are still in reasonable good condition.